Road Flood Warning Detection Using Wireless Sensors and Fuzzy Logic to Support Gresik Smart City - Frayudha, Angga Debby (Department of Informatics Engineering, 2024)
In this paper, we study how to overcome the urgency of flooding that occurs suddenly around the city of Gresik using wireless sensors with fuzzy logic to support Gresik smart city. The process of making flood alarm detection is very difficult to solve. To overcome this, we propose the use of wireless sensors using fuzzy logic in flood-prone areas. Fuzzy logic is used to process sensor data to find more accurate results to improve accuracy and efficiency. Two sensors are installed at the flood warning test point, using Wemos D1 MINI / NodeMCU so that the IoT network can be connected to the server. The data obtained from the measurement results are processed using fuzzy logic. Fuzzy will provide flood warnings automatically when the height is 30 cm and above. The method used is qualitative and product development research. The results after conducting 100 trials showed that there were six cases of errors in reading the water level, so that from the trial an error of 6% was obtained from the sensor made and a success accuracy of 94% was obtained. The research conducted concluded that the research results were as expected. In this way, public safety against sudden flood events will increase.